2013
DOI: 10.3390/ijerph10094104
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use and Environmental Smoke Exposure among Taiwanese Pregnant Smokers and Recent Quitters: Risk Perception, Attitude, and Avoidance Behavior

Abstract: In this study, we conducted an empirical survey of the avoidance behaviors and risk perceptions of active and passive smoking pregnant smokers and recent quitters. We employed an online questionnaire survey by recruiting 166 voluntary participants from an online parenting community in Taiwan. The results of the empirical survey revealed that three-fourths of smokers quit smoking during pregnancy and one-fourth continued smoking. All pregnant women who continued smoking had partners or lived with relatives who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 22 publications
(26 reference statements)
2
33
0
Order By: Relevance
“…Their results showed that the quitters had a greater awareness of the threat of smoking to fetal health ( quitter = 6.46 > smoker = 6.09, p < 0.05; one-tailed), severity of the threat of smoking to fetal health ( quitter = 6.35 > smoker = 5.72, p < 0.01; one-tailed), and overall perceived risk ( quitter = 6.40 > smoker = 5.90, p < 0.01; one-tailed) compared with the smoker group. Many pregnant women in their study were aware of the health risks of secondhand smoke to their unborn babies [20].In our study 84.4% of the smokers during pregnancy agreed to threat of active and passive smoking to the fetal health (Table 1). Nicotine activates multiple biologic pathways that are relevant to fetal growth and development, immune function, the cardiovascular system, the central nervous system, and carcinogenesis.…”
Section: Resultsmentioning
confidence: 72%
“…Their results showed that the quitters had a greater awareness of the threat of smoking to fetal health ( quitter = 6.46 > smoker = 6.09, p < 0.05; one-tailed), severity of the threat of smoking to fetal health ( quitter = 6.35 > smoker = 5.72, p < 0.01; one-tailed), and overall perceived risk ( quitter = 6.40 > smoker = 5.90, p < 0.01; one-tailed) compared with the smoker group. Many pregnant women in their study were aware of the health risks of secondhand smoke to their unborn babies [20].In our study 84.4% of the smokers during pregnancy agreed to threat of active and passive smoking to the fetal health (Table 1). Nicotine activates multiple biologic pathways that are relevant to fetal growth and development, immune function, the cardiovascular system, the central nervous system, and carcinogenesis.…”
Section: Resultsmentioning
confidence: 72%
“…(15) Pregnant women who live with smokers in their families are more exposed to the use of tobacco, and the association with smoking is a risk factor for the early use of tobacco. (2) Similarly, pregnant women who had a diagnosis of mental disorder and have received some specialized treatment tend to use tobacco, and have more difficulties to stop their use than those without mental disorders. Presence of depressive symptoms and no help in mental disease or smoking cessation makes the cessation of its use more complex, with predictable consequences to the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Considering women who use tobacco during pregnancy, in Brazil, it is estimated that 9.14% of pregnant women are also smokers, at considerable risk to her and the fetus health. (3) Risks include ectopic pregnancy, placenta abruption, ruptured membranes and placenta previa.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations